Subsurface Corrosivity Assessment Using Subsoil Resistivity in a Typical Basement Terrain: A Case Study of the Adebowale Area in Akure, Southwestern Nigeria - Adeyemo, Igbagbo Adedotun; Korode, Fuad Olamilekan; Olaniyan, Opeyemi Abiodun; Faleye, Oluseye Emmanuel (Indonesian Journal of Earth Sciences, 2024)
The aim of this study is to investigate and map the subsurface corrosivity of soils at various depths (0.5 - 3.0 m) within the Adebowale community in Akure, Southwestern Nigeria, and to identify safe zones for the burial of metallic objects based on soil resistivity measurements. Sixty vertical electrical sounding (VES) data points were acquired using the Schlumberger electrode array with half-current (AB/2) spacing ranging from 1 - 150/225 m. The VES survey delineated 3 - 5 subsurface layers across the study area, corresponding to topsoil, weathered layer, partially weathered basement, fractured basement, and fresh basement. Maps of longitudinal conductance, longitudinal resistivity, and iso-resistivity depth slices (0.5, 0.75, 1.0, and 3.0 m) were generated. The corrosivity of the subsoil in the study area was categorized into five types: very high corrosivity (< 50 ?m), high corrosivity (50 - 100 ?m), moderate corrosivity (100 - 150 ?m), low corrosivity (150 - 200 ?m), and negligible corrosivity (> 200 ?m). At 1.0 m and 3.0 m depth surfaces, the areas of negligible to low corrosivity are about 70% and 85%, respectively, suggesting that corrosivity decreases with depth within the shallow subsurface of the study area. The longitudinal conductance and longitudinal resistivity maps of Adebowale indicated that the areas of negligible to low corrosivity are about 85% and 75%, respectively, corroborating the depth slice resistivity maps. In these areas, buried metallic utilities are safe; conversely, any metallic utilities buried within the moderate to very high corrosivity zones of the study area must be adequately protected to avoid corrosion.